1974
DOI: 10.1126/science.186.4158.47
|View full text |Cite
|
Sign up to set email alerts
|

Rod and Cone Pathways in the Inner Plexiform Layer of Cat Retina

Abstract: In cat retina, rod bipolar terminials do not synapse on ganglion cells but on two types of amacrine cell (types I and II). Cone bipolars synapse directly on ganglion cells and on type I amacrines. The type II amacrine appears to play a special internuncial role between bipolars and ganglion cells in the rod system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
354
1
2

Year Published

1986
1986
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 455 publications
(370 citation statements)
references
References 15 publications
13
354
1
2
Order By: Relevance
“…The AI1 and Al 7 amacrine cells receive many synapses from the rod bipolar neuron (M. A. Freed, unpublished observations; Kolb and Famiglietti, 1974;Kolb and Nelson, 1983;Sterling, 1983); therefore it is plausible that pathways leading from the rod bipolar might carry the rod signal over the scotopic range of intensities (Sterling, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…The AI1 and Al 7 amacrine cells receive many synapses from the rod bipolar neuron (M. A. Freed, unpublished observations; Kolb and Famiglietti, 1974;Kolb and Nelson, 1983;Sterling, 1983); therefore it is plausible that pathways leading from the rod bipolar might carry the rod signal over the scotopic range of intensities (Sterling, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…(Famiglietti and Kolb, 1975;Kolb 1979;Kolb and Famiglietti 1974;Strettoi et al, 1990Strettoi et al, , 1992. The synaptic input from rod bipolar cells is located at the arboreal dendrites in sublamina b of the IPL.…”
Section: The Aii Amacrine Cell In the Mammalian Retinamentioning
confidence: 99%
“…The first evidence for potential electrical synapses between AII amacrine cells came from ultrastructural studies of cat retina (Famiglietti and Kolb, 1975;Kolb and Famiglietti, 1974). These studies defined the AII amacrine cells as such and demonstrated several of their synaptic contacts.…”
Section: Homologous Gap Junctions Between Aii Amacrine Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bipolar cell synaptic inputs account for 35% of the total observed. In addition, rod bipolar cell terminals, easily identified by their cytologic characteristics in mammalian retinae (Kolb and Famiglietti, 1974;Famiglietti and Kolb, 1975;Kolb, 1979;McGuire et al, 1984McGuire et al, , 1986, did not synapse onto Y1-immunoreactive amacrine cell processes. These findings indicate that Y1-immunoreactive amacrine cell processes receive bipolar cell axonal input, although which cone bipolar cell types (Euler and Wässle, 1995;Hartveit, 1996) provide this input remains to be determined.…”
Section: Synaptic Connectivity Of Y1-immunoreactive Amacrine Cells Inmentioning
confidence: 99%